UV-modified polydopamine zincophilic protective layer for durable and alkaline-stable zinc anodes in zinc-air batteries - Kurian, Maria; Pandikassala, Ajmal; Kurungot, Sreekumar (Journal of Materials Chemistry A, 2025)
Rechargeable zinc-air batteries (ZABs) are promising for flexible energy storage due to their high specific energy, safety, and cost-effectiveness. However, the snags of the zinc (Zn) anode, like ineluctable passivation and dissolution in strongly alkaline electrolytes, limit the discharge and cycling performance of the battery. Electroless plating can be employed to coat the Zn foil with a polydopamine (PDA) layer, leveraging PDA's strong adsorption on the Zn via bidentate bonds. Due to PDA's poor stability in alkaline media, ultraviolet (UV)-induced secondary modifications are conducted to obtain Zn@PDA-UV electrodes with enhanced mechanical and chemical stability. The Zn@PDA-UV layer regulates Zn dendrite growth and suppresses hydrogen evolution and passivation. The zincophilic groups on the Zn@PDA-UV anode suppressed the zincate cross-over, enhancing the recyclability of the ZABs. When paired with commercial catalysts to assemble alkaline ZABs, the battery displayed excellent cycling stability of 75 h. A highly stable anion-conducting polymer electrolyte membrane (PXM) was prepared from the polymer blend of polyvinyl alcohol (PVA), xanthan gum, and METAC monomers to tailor a high-performing flexible ZAB with suppressed zincate crossover. The flexible ZAB, integrating the modified Zn anode and PXM, shows a stable cycling profile under various bending angles, demonstrating excellent mechanical and electrochemical durability.